Computed Tomography (CT)-Assisted 3D Cephalometry in Horses: Interincisal Angulation of Clinical Crowns - Kau, Silvio; Failing, Klaus; Staszyk, Carsten (Frontiers in Veterinary Science, 2020)
The angle encompassed between opposing incisors in horses is assumed to decline with age. Previous studies merely consider the overall profile view of clinical crowns presuming a generalized angle neglecting potential tooth position-dependent differences. Cephalometric measurements from 3D computed tomographic thick-slab reconstructions of single incisors within a global reference frame were used to determine clinical crown interincisal angulation (IIA) of 48 horses. Based on predefined dentoalveolar landmarks, IIA was defined as the angle enclosed by the respective labial axis of the clinical crown (LACC). A measurement repeatability analysis was conducted including a comparison of corner incisor IIA with data obtained by cephalometric implementation of previously described landmarks for corner incisors (lingual/ palatal border). The age-related angle course and differences between tooth positions were investigated considering LACCs of permanent incisors. Determining IIA by LACCs exhibited a high level of reproducibility applying for all tooth positions (mean coefficient of variation = 0.65 %; mean SD ± 0.89°). The comparison method for corner incisors revealed two times higher mean dispersion of repeated measurements, P = 0.017. A nonlinear model slightly increased predictability of angular changes over time as against linearity assumption. The angle decline was more distinctive in younger horses and appears to approach a final value in older ones. Corner incisors exhibited significantly higher angle decline compared to central and middle incisors, P < 0.0001. According to the results, age determination of horses using clinical crown IIA is not recommended. Rather, 3D cephalometry may provide a promising tool to determine interdental and dentofacial angles of distinct tooth positions in health and disease.